Temperature Related Absorption and Excretion of Sulphadimidine in Rainbow Trout, Salmo Gairdneri - Borgan, Anne (Acta Vet Scand, 1981)
The main purpose of the present study was to see if a kinetic model and a computer program for characterizing the rate of uptake and clearance of chemicals in aquatic organisms (Biofac, OECD’s Chemicals Testing Programme) was applicable to pharmacokinetic studies in fish. The program seems suitable for such studies. The effect of temperature upon rate of absorption of sulphadimidine from medicated water and elimination of the same drug was investigated in rainbow trout. A rise in the temperature from 7° C to 14° C more than doubled the calculated rate constants of absorption and elimination. The biological half life (t(½) β) and the time to reach 90 % of steady state (t(90% ss)) at 14° C were approximately half the values at 7° C.